2014
DOI: 10.1158/0008-5472.can-14-0968
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled Inflammation Induced by AEG-1 Promotes Gastric Cancer and Poor Prognosis

Abstract: Gastric cancer is one of the most common causes of cancer-related death worldwide. Helicobacter pylori infection plays an important role in the development and progression of gastric cancer. The expression of astrocyte-elevated gene-1 (AEG-1) is increased in gastric cancer tissues, thereby contributing to the inflammatory response. We investigated whether and how AEG-1 regulated proinflammatory signaling in gastric cancer cells. We used human gastric cancer cell lines and athymic nude mice to investigate the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 48 publications
1
57
0
Order By: Relevance
“…Gene chip analysis reveals that AEG-1 overexpression leads to up-regulation of several NF-κB downstream genes, including IL-6 [9]. Consistent with the findings of previous research [9], another study demonstrates that AEG-1 knockdown could lead to the inactivation of NF-κB and down-regulation of MMP-9 [32]. Consistent with previous study [14], we showed that AEG-1 was required for NF-κB p65 activation in macrophages.…”
Section: Discussionsupporting
confidence: 64%
“…Gene chip analysis reveals that AEG-1 overexpression leads to up-regulation of several NF-κB downstream genes, including IL-6 [9]. Consistent with the findings of previous research [9], another study demonstrates that AEG-1 knockdown could lead to the inactivation of NF-κB and down-regulation of MMP-9 [32]. Consistent with previous study [14], we showed that AEG-1 was required for NF-κB p65 activation in macrophages.…”
Section: Discussionsupporting
confidence: 64%
“…28). Cell lines were authenticated by cell viability analysis, short tandem repeat profiling, and isoenzyme analysis.…”
Section: Cell Culturementioning
confidence: 99%
“…Since these inflammatory mediators are also upregulated during aging, they may be driving AEG-1 expression during the aging process. Consequently, the fundamental participation of AEG-1 in inflammatory responses through the regulation of NF-κB pathway (Emdad et al , 2006; Li et al , 2014b; Sarkar et al , 2008) designates AEG-1 as a critical immune modulator in aging and age-related diseases (Fig. 3).…”
Section: Astrocytes and Aeg-1 In Agingmentioning
confidence: 99%